Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) di Sekolah Dasar - Oklin Adetya; Desyandri Desyandri (Universitas Negeri Padang, 2020)
The purpose of this study is to describe the increase in integrated thematic learning outcomes using the Problem Based Learning model in class V SDN 03 Pakan Kurai Bukittinggi City. This type of research is Classroom Action Research using qualitative and quantitative approaches. The subjects of the research were teachers and 28 fifth grade students of SDN 03 Pakan Kurai Bukittinggi. The use of Problem Based Learning models can improve student learning outcomes in integrated thematic learning, this can be seen from the assessment of RPP aspects in the first cycle is 90,28% increased in the second cycle to 94,44%. The implementation of learning in the aspect of the first cycle teacher that is 85.71% increased to 92.85% in the second cycle and from the aspect of the first cycle students is 82,14% increased to 92.85% in the second cycle, while the learning outcomes of the students on first cycle is80,44 increased to 85.06 in the second cycle.